Platelet pannexin-1 channels modulate neutrophil activation and migration but not the progression of abdominal aortic aneurysm - Metz, Lisa Maria; Feige, Tobias; de Biasi, Larissa; Ehrenberg, Agnes; Mulorz, Joscha; Toska, Laura Mara; Reusswig, Friedrich; Quast, Christine; Gerdes, Norbert; Kelm, Malte; Schelzig, Hubert; Elvers, Margitta (Frontiers in Molecular Biosciences, 2023)
Abdominal aortic aneurysm (AAA) is a common disease and highly lethal if untreated. The progressive dilatation of the abdominal aorta is accompanied by degradation and remodeling of the vessel wall due to chronic inflammation. Pannexins represent anion-selective channels and play a crucial role in non-vesicular ATP release to amplify paracrine signaling in cells. Thus, pannexins are involved in many (patho-) physiological processes. Recently, Panx1 channels were identified to be significantly involved in AAA formation through endothelial derived Panx1 regulated inflammation and aortic remodeling. In platelets, Panx1 becomes activated following activation of glycoprotein (GP)VI. Since platelets play a role in cardiovascular diseases including AAA, we analyzed the contribution of platelet Panx1 in the progression of AAA. We detected enhanced Panx1 plasma levels in AAA patients. In experimental AAA using the pancreatic porcine elastase (PPE) mouse model, a major contribution of platelet Panx1 channels in platelet activation, pro-coagulant activity of platelets and platelet-mediated inflammation has been detected. In detail, platelets are important for the migration of neutrophils into the aortic wall induced by direct cell interaction and by activation of endothelial cells. Decreased platelet activation and inflammation did not affect ECM remodeling or wall thickness in platelet-specific Panx1 knock-out mice following PPE surgery. Thus, aortic diameter expansion at different time points after elastase infusion of the aortic wall was unaltered in platelet-specific Panx1 deficient mice suggesting that the modulation of inflammation alone does not affect AAA formation and progression. In conclusion, our data strongly supports the role of platelets in inflammatory responses in AAA via Panx1 channels and adds important knowledge about the significance of platelets in AAA pathology important for the establishment of an anti-platelet therapy for AAA patients.